The Role of New Educational Technologies in Teachers’ Professional Preparation in Higher Education - ALEKSANYAN, ANNA (Journal of Education, Technology and Computer Science, 2018)
Numerous pedagogical technologies have been developed and presented in modern pedagogy, such are: pedaogical-educational organization ways, learning technologies, as well as a combination of methods, knowledge, abilities, skills, and resources in the common use of education management systems. Based on the concepts of the education system, we can say, that education management technology provides a unified effective functioning of intercommunication components due to the communication network.